Apical Takotsubo syndrome versus anterior acute myocardial infarction: findings from the Tokyo Cardiovascular Care Unit network registry. Issue 1 (February 2019) - Isogai, Toshiaki; Yoshikawa, Tsutomu; Ueda, Tetsuro; Yamaguchi, Tetsuo; Imori, Yoichi; Maekawa, Yuichiro; Sakata, Konomi; Murakami, Tsutomu; Mochizuki, Hiroki; Arao, Kenshiro; Kimura, Akihisa; Nagao, Ken; et al.
Background: Although the typical apical form of Takotsubo syndrome and anterior acute myocardial infarction have similar electrocardiographic and echocardiographic presentations, data on the clinical differences between the two disorders are limited. Methods: Using the Tokyo Cardiovascular Care Unit network registry, we identified patients hospitalised with apical Takotsubo syndrome ( n =540; 2010–2014) or anterior acute myocardial infarction ( n =2, 806; 2013–2014) and created 522 age and sex-matched pairs (mean age 74.1 years; women 78.5%). We compared the clinical characteristics and inhospital outcomes between the two groups. Results: On admission, patients with apical Takotsubo syndrome showed a lower body mass index, less frequent chest pain/tightness, lower systolic blood pressure, higher heart rate, lower creatine kinase, higher C-reactive protein and brain natriuretic peptide, and less frequent ST-elevation than patients with anterior acute myocardial infarction. Patients with apical Takotsubo syndrome received catecholamine (12.8% vs. 24.5%, P <0.001) and intra-aortic balloon pumping (5.9% vs. 15.1%, P <0.001) less frequently. Despite similar all-cause mortality (5.4% vs. 7.9%, P =0.134), patients with apical Takotsubo syndrome showed lower cardiac mortality (2.1% vs. 6.7%, P <0.001; risk difference −4.6% (95% confidence interval −7.1% to −2.1%)) but higher non-cardiac mortality (3.3% vs. 1.1%, P =0.033; 2.1% (0.3%–3.9%)). In subgroup comparisons, patients with physically triggered Takotsubo syndrome had higher non-cardiac mortality (7.0%) than those with non-physically triggered Takotsubo syndrome (1.2%, P =0.001) or anterior acute myocardial infarction (1.1%, P <0.001). Conclusions: This study found that cardiac and non-cardiac mortality risks differed significantly between apical Takotsubo syndrome and anterior acute myocardial infarction. Our findings underscore the importance of differentiating between the two disorders for appropriate management.